2015
DOI: 10.1016/j.jcrysgro.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and spectroscopic performance of large crystalline boules of CsCaI3:Eu scintillator

Abstract: a b s t r a c tThe crystal growth of CsCaI 3 :Eu with improved quality over prior efforts for use in X-ray and gamma-ray detection applications is reported. Boules were grown using the vertical Bridgman technique in quartz ampoules at 15, 22, and 35 mm diameters. CsCaI 3 :Eu crystals show evidence of a heavily twinned microstructure likely caused by a solid-solid phase transformation of the crystal during the cooling process. Energy resolution (FWHM) in large and small samples taken from crystalline boules var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
(18 reference statements)
3
11
0
Order By: Relevance
“…And while the twinning does not appear to affect the optical transparency of the crystals it may have some effect on the scintillation performance. Similar twinning can be observed in other metal halide scintillator crystals like europium doped cesium calcium iodide (CsCaI 3 : Eu) [15]. The twinning in CsSrBr 3 is thought to arise due 233 to a solid-solid phase transition.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…And while the twinning does not appear to affect the optical transparency of the crystals it may have some effect on the scintillation performance. Similar twinning can be observed in other metal halide scintillator crystals like europium doped cesium calcium iodide (CsCaI 3 : Eu) [15]. The twinning in CsSrBr 3 is thought to arise due 233 to a solid-solid phase transition.…”
supporting
confidence: 55%
“…This insures a flat or convex interface, both 105 of which are better suited for improved crystal growth. Previous crystal growth experiments 106 carried out in a transparent furnace have suggested that the use of a diaphragm also minimizes 107 the migration of the growth interface due to a heat sinking effect of the charge, which may cause 108 the growth rate to fluctuate over time [15]. The crystal was then grown by translating the 109 ampoule through the furnace at a pulling rate of 0.5 mm/hour.…”
mentioning
confidence: 99%
“…In principle, the perovskite structure can be retained by using homovalent Pb replacements. In practice, however, the substitution of Pb by other divalent metals in the Periodic Table leads either to unstable perovskites or to stable semiconductors with band baps larger than 2.7 eV, , such as halide perovskites based on the alkali earth metals Ca, Sr, or Ba. …”
Section: Introductionmentioning
confidence: 99%
“…Instantaneous thermal stresses may promote cracking, as posited by the prior studies referred to above [9][10][11][12][13], and the important role of such thermal stresses on cracking has been documented in many prior experimental studies [14][15][16][17][18][19][20][21][22][23]. However, a solid can also experience residual stresses remaining in the material after the original cause has been removed [24] that can delay cracking to during unloading or processing.…”
Section: Introductionmentioning
confidence: 99%